Pengaruh Pengungkapan Corporate Social Responsibility (CSR) Terhadap Nilai Perusahaan Dengan Profitabilitas Sebagai Variabel Moderasi Pada Perusahaan Pertambangan - Anam, Hairul; Lusy, Lusy (Jurnal GeoEkonomi, 2026)
This research aims to determine the effect of Corporate Social Responsibility (CSR) disclosure on company value with profitability as a moderating variable in mining companies listed on the Indonesia Stock Exchange in 2020-2022. Based on the results of the research that has been carried out, it shows that disclosure of Corporate Social Responsibility (CSR) influences Company Value, while Profitability is unable to moderate the influence of Corporate Social Responsibility (CSR) disclosure on Company Value.